County-level urban forms and their correlation with local governance in Jiande, China: evidence from historical records - Yuan Sun; Yiqun Wu; Huifang Yu; Yonghua Li (Journal of Asian Architecture and Building Engineering)
Examining the morphological evolution of ancient Jiande County (JD) over time, our research adopts a diachronic perspective to explore county-level spatial planning and its correlations with local governance during the feudal and republican eras. Utilizing historical records, including chronicles, geo-maps, and remote sensing images, to reconstruct urban ground plans, our findings unveil a historical shift in administrative management within the ancient Yanzhou region (YZ). In the Song Dynasty, feudal authority was distinctly manifested through a spatial hierarchy, diminishing in influence during the Ming-Qing Dynasty. In contemporary times, Meicheng Town (the ancient Jiande County) has departed from traditional urban layouts, relinquishing its central position in the local administrative hierarchy. JD’s historic transition in county-level urban planning and local governance paradigms provides evidence for examing its future development trajectories.